PEMANFAATAN LAHAN PEKARANGAN RUMAH DENGAN PENERAPAN IPTEK BUDIDAYA ANGGUR NINEL DAN ANGGUR AKADEMIK BAGI MASYARAKAT DI KELURAHAN TERATAI KECAMATAN MUARA BULIAN KABUPATEN BATANG HARI - Sophia, Sophia; Varina, Firna; Tukidi, Tukidi; Laksono, Bangun Joko; Armando, Reno (Fakultas Pertania Universitas Muara Bungo, 2023)
Grapes are one of the prima donna plants in tropical climates, but the cultivation techniques are not widely known by the general public, especially when cultivated in the yard. Teratai Village, Muara Bulian District, has a tropical climate which is quite supportive of grape cultivation. Many people's home gardens have potential but are not utilized optimally for cultivating useful fruit plants. Because of this, we are holding community empowerment activities through the use of house yards by applying science and technology for cultivating Ninel and Academic grape varieties to the residents. The implementation of this dedication will later be very beneficial for the knowledge, creativity of residents in utilizing the yard of the house and the realization of the wine village area. The method of implementing the service is carried out by providing counseling and direct demonstrations on making planting media, making organic fertilizer specifically for grapes, cultivation techniques, and grapevine care techniques. The results of the implementation of the service are the adoption, interest, knowledge, innovation, and creativity of the residents in utilizing the yard of the house with grape cultivation techniques, and the achievement of efforts to increase the income of the residents' households. This community service activity was successful, as evidenced by the fact that dozens of residents and the Teratai Village administration who were invited were fully present at each stage of the activity, resulting in an increase in the knowledge, innovation and creativity of the residents regarding the cultivation of ninel grapes and academic grapes in their yards.